SYNTHESIS AND CHARACERISATION OF NOVEL PENTADENTATE LIGAND TYPE N2S2O 4-METHYL-2,6- BIS[4-METHYL THIOSEMICARBAZONYLIDEN]- PHENOL AND THEIR COMPLEXES WITH Ni+2 , Pd+2 , Cu+2 , Zn+2 , Cd+2 and Hg+2
Two equivalent of 4-methyl thiosemicarbazide was reacted with 2,6-diformyl-4-methyl phenol to give the new pentadentate ligand H3L type N2S2O where H3L= 4-methyl-2,6- Bis[4-methyl thiosemicarbazonyliden]-phenol. Also complexes of the ligand of H3L in general formula [M HnLX]y where M=Ni+2 , Cu+2